DIFFERENTIATED LEARNING BASED ON UNDERSTANDING BY DESIGN (UbD) AND AI TO IMPROVE WRITING SKILL - sugeng ariadi, eka (SEAQIL Journal of Language Education, 2024)
Writing skill is a skill that is highly emphasized so that Indonesian students can truly master it in today's digital era. In learning English at MA level, writing skill on report text is highly prioritized, but this cannot be felt by students in class X-I MAN 1 Pasuruan. For this reason, researchers carried out best practice learning by implementing differentiated learning based on artificial intelligence-based UbD design in this class. The aim of this best practice is to improve the writing skill of students in class X-I MAN 1 Pasuruan on the material report text. After this best practice was carried out, several conclusions were obtained. First, the learning results show that students are happy with the provision of cognitive and non-cognitive diagnostic assessments to become aware of their respective learning styles. Second, the use of LKPD has not made students interested in enjoying the learning process. Finally, students stated that they could understand the material provided eventhough they were not completely happy with it. Suggestions and recommendations from this best practice are that the differentiated learning approach is worthy of being practiced by educators wherever they are and really needs to be integrated with other learning approaches or strategies or methods and of course also taking advantage of technological developments in learning.